Comparative Study of Construction Contract Dispute Resolution Mechanisms between Indonesia and Singapore - Natasya Yunita Sugiastuti; Ani Purwati; Wardatul Fitri; Salwa Faeha Hanim; Selamat Lumban Gaol (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study examines and compares the legal foundations and practical mechanisms for resolving construction contract disputes in Indonesia and Singapore, an area where in-depth comparative research remains limited. The study aims to analyze similarities and differences in the legal frameworks, institutional arrangements, and procedural effectiveness of dispute resolution in both jurisdictions, and to explore how Singapore’s practices might inform reform in Indonesia. Using a qualitative socio-legal approach with a comparative research design, data were collected from statutory regulations, case law, and doctrinal literature, supplemented by semi-structured interviews with legal practitioners, arbitrators, and adjudicators in both countries. Findings show that Singapore’s framework, anchored by the Building and Construction Industry Security of Payment Act (SOPA) and the Singapore International Arbitration Centre (SIAC), delivers faster resolution timelines and greater predictability through specialized statutory adjudication, whereas Indonesia’s system, governed by Law Number 2 of 2017 on Construction Services and BANI arbitration rules, remains hampered by procedural delays and limited enforcement efficiency. Singapore’s statutory adjudication model therefore offers a viable reference point for reforming Indonesia’s construction dispute resolution regime, with potential to enhance legal certainty, efficiency, and investor confidence.